2015
DOI: 10.5051/jpis.2015.45.6.223
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility and pathogenic genes ofStaphylococcus aureusisolated from the oral cavity of patients with periodontitis

Abstract: PurposeThe goal of this study was to characterize the patterns of antimicrobial resistance and virulence genes in samples of Staphylococcus aureus (S. aureus) isolated from periodontitis patients.MethodsFrom July 2015 to August 2015, oral saliva was collected from a total of 112 patients diagnosed with periodontitis, including 80 outpatients in dental hospitals and 32 patients in dental clinics located in Seoul and Cheonan. The samples were subjected to a susceptibility test to evaluate the prevalence of antim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 19 publications
2
23
1
6
Order By: Relevance
“…All 30 coagulase positive isolates of S. aureus were subjected to antibiotic susceptibility test and the results revealed that 93.33% isolates were found resistant to penicillin followed by 90% to amoxicillin, 83.33% to ampicillin and 33.33% to erythromycin where 80% sensitive to cephradine, 63.33% to ciprofloxacin, and 60% to erythromycin (53.33%) ( Table 3). Kim and Lee (2015) reported that S. aureus isolated from the periodontal patients showed 88% (36/41) isolates resistant to penicillin and ampicillin which is comparable to the present study. They also observed the susceptibility rate and found 98% isolates susceptible to cefotetan, 95% to ciprofloxacin and 90% to tetracycline and erythromycin that is comparatively higher than the current study.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…All 30 coagulase positive isolates of S. aureus were subjected to antibiotic susceptibility test and the results revealed that 93.33% isolates were found resistant to penicillin followed by 90% to amoxicillin, 83.33% to ampicillin and 33.33% to erythromycin where 80% sensitive to cephradine, 63.33% to ciprofloxacin, and 60% to erythromycin (53.33%) ( Table 3). Kim and Lee (2015) reported that S. aureus isolated from the periodontal patients showed 88% (36/41) isolates resistant to penicillin and ampicillin which is comparable to the present study. They also observed the susceptibility rate and found 98% isolates susceptible to cefotetan, 95% to ciprofloxacin and 90% to tetracycline and erythromycin that is comparatively higher than the current study.…”
Section: Resultssupporting
confidence: 90%
“…The percentage of S. aureus isolated from human dental infection is more frequent as the findings of Ohara-Nemoto et al 2008reported 46.4%. McCormack et al (2015) and Kim and Lee (2015) reported 18 and 36.6% S. aureus in human oral and perioral infections that is comparatively lower than the current results.…”
Section: Resultscontrasting
confidence: 87%
“…S. aureus is often carried within the nares and on the skin of colonized hosts. Although S. aureus is generally thought to be a noncommensal, increasing numbers of culture and molecular-based studies have shown that this pathogenic species is more common on mucosal surfaces from healthy subjects than originally hypothesized (87)(88)(89)(90)(91)(92)(93)(94)(95)(96)(97). While this pathogen may not directly contribute to localized mucosal virulence in the oral cavity, the transient or persistent carriage of S. aureus on various mucosal surfaces can provide an infectious source for systemic disease, particularly when C. albicans is present (…”
Section: Candida-mycobacterium Tuberculosismentioning
confidence: 99%
“…Enterococcus faecalis, on the other hand, plays a pivotal role in establishing a microbial community by connecting various bacteria in the oral cavity [5][6][7] . Staphylococcus aureus, a Gram-positive staphylococcus typically found in the respiratory system, on the skin, and in the oral cavity, is also found in the periodontium where it may cause periodontal disease 8,9) . Candida albicans, the most common fungus in the oral cavity and the gastrointestinal tract, causes opportunistic infections by quickly expanding due to host environmental changes induced by various factors 10,11) .…”
Section: Introductionmentioning
confidence: 99%